Faces of Geometry. From Agnesi to Mirzakhany (diségno, 2019)
The 12th of May is the day dedicated to the worldwide celebration of women in mathematics , coordinated by EWM, European Women in Mathematics, and supported by the African Women in Mathematics Association, by the Colectivo de Mujeres Matematicas de Chile, by the Indian Women and Mathematics and finally, by the Women’s Commit- tee of the Iranian Mathematical Society, which was founded with the intention of promoting the dissemination of the contribution that women have provided to research in the area of this discipline and its many applications, which unfortunately has not yet been properly acknowledged. (read more)